Unraveling the genetic links between obesity or insulin resistance and breast cancer through the impact of CD295 and ITLN1 SNPs with DNA damage in a case-controlled study with bioinformatics analysis - Hamdy, Nadia M.; Mosaad, Yasser O.; Elshimy, Reham; Hady, Ahmad A.; Lin, Queran; Jastaniah, Zayd; Amjad, Razan; Altoukhi, Huda; Almarzouki, Hatim; Abdelsamad, Ahmed; El Magdoub, Hekmat M.; Fathi, Doaa (Frontiers in Medicine, 2025)
BackgroundMutations in the cluster of differentiation (CD) 295 gene, which encodes a class I cytokine receptor, are associated with obesity and breast cancer (BC). Single-nucleotide polymorphisms (SNPs) in the adipocyte-inferred novel cytokine intelectin 1 (ITLN1) remain understudied in connection to CD295 polymorphisms and diabetes mellitus (DM) or a pre-diabetic state, as well as to DNA damage seen in BC.AimTo explore whether CD295 (rs6700986) and ITLN1 (rs952804) SNPs impact BC with or without DM, insulin resistance (IR), or obesity. Effects of ITLN1 or CD295 polymorphism(s) on DNA damage in BC were also examined. All of these are to be confirmed by bioinformatics/in silico analysis.Subjects and methodsBlood samples from 170 women with BC (including 33 and 48 with DM and pre-diabetes, respectively) and from 108 age-matched women in the control group were collected. Plasma insulin, leptin, CD295, and ITLN1 levels were measured by ELISA. rs6700986 and rs952804 were analyzed by RT-PCR. DNA damage was assessed using the alkaline comet assay.ResultsBC cases with clinical stage T II and positive LN, as well as tumor histologic grade III, presence of obesity, pre-diabetic events, DM, or IR, were associated with CD295 rs6700986 mutant homozygous (CC) and heterozygous (CT) genotypes and ITLN1 rs952804 mutant CT genotype (p ≤ 0.05). Tail DNA (%) and tail moment units were significantly associated with the CD295 rs6700986 CT and the ITLN1 rs952804 TT genotypes. The C allele (CT + CC vs. TT) and T allele (TT + CT vs. CC) for CD295 rs6700986 and ITLN1 rs952804, respectively, were associated with BC risk (p ≤ 0.05).ConclusionCD295 (rs6700986) and ITLN1 (rs952804) SNPs should be considered as BC-associated susceptibility risk factors in obese, insulin resistance, or pre-diabetic individuals.